Government and not-for-profit accounting : concepts and practices - Granof, Michael H. (Hoboken, NJ : Wiley, 2007)
This book makes people to be aware of the dynamism of government and not-to-profit accounting and of intellectual challenges that it presents.
aia 09/05/13
Loan
Keywords: Finance, Public -- United States -- Accounting; Finance, Public -- Accounting -- Standards -- United States; Nonprofit organizations -- United States -- Accounting; Nonprofit organizations -- Accounting -- Standards -- United States